Homologs of the Acinetobacter baumannii AceI Transporter Represent a New Family of Bacterial Multidrug Efflux Systems - Karl A. Hassan (American Society for Microbiology, 2015)
ABSTRACT Multidrug efflux systems are a major cause of resistance to antimicrobials in bacteria, including those pathogenic to humans, animals, and plants. These proteins are ubiquitous in these pathogens, and five families of bacterial multidrug efflux systems have been identified to date. By using transcriptomic and biochemical analyses, we recently identified the novel AceI (Acinetobacter chlorhexidine efflux) protein from Acinetobacter baumannii that conferred resistance to the biocide chlorhexidine, via an active efflux mechanism. Proteins homologous to AceI are encoded in the genomes of many other bacterial species and are particularly prominent within proteobacterial lineages. In this study, we expressed 23 homologs of AceI and examined their resistance and/or transport profiles. MIC analyses demonstrated that, like AceI, many of the homologs conferred resistance to chlorhexidine. Many of the AceI homologs conferred resistance to additional biocides, including benzalkonium, dequalinium, proflavine, and acriflavine. We conducted fluorimetric transport assays using the AceI homolog from Vibrio parahaemolyticus and confirmed that resistance to both proflavine and acriflavine was mediated by an active efflux mechanism. These results show that this group of AceI homologs represent a new family of bacterial multidrug efflux pumps, which we have designated the proteobacterial antimicrobial compound efflux (PACE) family of transport proteins. IMPORTANCE Bacterial multidrug efflux pumps are an important class of resistance determinants that can be found in every bacterial genome sequenced to date. These transport proteins have important protective functions for the bacterial cell but are a significant problem in the clinical setting, since a single efflux system can mediate resistance to many structurally and mechanistically diverse antibiotics and biocides. In this study, we demonstrate that proteins related to the Acinetobacter baumannii AceI transporter are a new class of multidrug efflux systems which are very common in Proteobacteria: the proteobacterial antimicrobial compound efflux (PACE) family. This is the first new family of multidrug efflux pumps to be described in 15 years.